Influence of Deep Root Density on Root Pulling Resistance in Rice - Ekanayake, I.J.; Garrity, D.P.; O'Toole, J.C. (Wiley, 1986)
Rooting patterns play an important role in determining the degree of resistance of rice (Oryza sativa L.) cultivars to water stress. Root pulling resistance (RPR) has been suggested as a technique to evaluate genotypic differences in root growth in rice. This work investigated the association between RPR and root length density of the unpulled root component (portion of the root system remaining in the soil after pulling). The rate of increase in RPR among rice cultivars with plant age was also examined. A clamp apparatus connected to a modified spring balance was attached to the base of the plant to measure the pulling resistance. Characteristics of the pulled (portion of the root system removed from the soil) and unpulled root components were assessed in five rice genotypes varying from drought sensitive to tolerant. Two genotypes (IRS2 and MGL2) recorded high RPR, two intermediate (IR 36 and IR442‐2‐58), and one had low RPR (IR20). Genotypes with high RPR were characterized by larger, thicker, and denser root systems. Pulling resistance was significantly correlated with root volume, dry weight, thickness, and the number of thick roots in the pulled root component. Several traits of the pulled root component also had highly significant positive correlations with root length density (RLD) at 0.3 to 0.6 m soil depth. However, RPR was most highly correlated with the RLD of the unpulled component, particularly the RLD from 0.45 to 0.6 m depth (r= 0.88**, significant at the 0.01 probability level). These results suggest that high RPR is strongly related to the ability of the plant to rapidly develop greater root penetration into deeper soil layers. They tend to confirm the utility of RPR as a practical technique in selection for superior root systems in a rice improvement program. Time course analysis of RPR among cultivars showed that genotypic differences increased with plant age. The rate of increase in RPR was low for the first 24 to 25 days after transplanting, but accelerated greatly after this date in tests over two seasons. This change in the rate of increase may correspond with the time at which the root system penetrates into the firm soil layers below the puddled layer. Among the dates used in the study, the optimum sampling date was 33 days after transplanting.